3D angle-interlock woven structural wearable triboelectric nanogenerator fabricated with silicone rubber coated graphene oxide/cotton composite yarn. (1st November 2020) - He, Enfang; Sun, Ya; Wang, Xuewei; Chen, Haijia; Sun, Baozhong; Gu, Bohong; Zhang, Wei
Abstract: The fabric-based triboelectric nanogenerator (TENG) with flexibility, diverse structure and energy harvesting aroused widespread concern in recent years for various portable electronics. Herein, a 3D angle-interlock woven (3DAW) structural wearable TENG with high output performance was fabricated with silicone rubber coated graphene oxide/cotton composite yarn. Composite yarn acts the role of energy conversion and it was fabricated to specific 3D woven structure to further improve its electrical properties. The optimal single yarn with a diameter of 2 mm demonstrates open-circuit voltage of 30.8 V and short-circuit current of 1.1 μ A using constant loading force tapping ( 10 N). The obtained 3DAW-TENG reveals the output power of 225 mW/m 2 with the area of 5 cm × 7 cm, which is more outstanding compared with those of 2D plain structure and 3D double-layer plain structure. The 3DAW-TENG also successfully shows the application in charging small electronics and triggering voltage sensors. It's suggested that the 3DAW-TENG can be a potential candidate for the filed of wearables and self-powered sensors.